Clinical analysis of 109 cases of lacrimal gland pleomorphic adenoma - Rui Liu (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To monitor the prognosis of patients with lacrimal gland pleomorphic adenoma (LGPA) following surgical resection within the past 10y. The factors affecting patient prognosis are analyzed and the experience of surgical treatment is summarized. METHODS: In this retrospective, comparative case series, clinical records from 109 cases of LGPA treated chiefly at the same institution between November 2009 and May 2019 were reviewed. All 109 patients underwent surgery, histopathological examination, and imaging examination. For patients who underwent surgery for the first time, LGPA could be resected completely, including tumor and capsule tissues, using a surgical approach via the eyebrow arch or double eyelid crease. RESULTS: The ratio of males to females was 1:1.60, the ages ranged from 19 to 74 years old with a mean age of 43.64±13.07 years old, and the ratio of left to right eyes was 1:1.37. A total of 109 patients underwent surgical excision and five of these received radiotherapy after malignant transformation. Of these patients, 15 were lost to follow up within the April 1, 2020 deadline and 1 was diagnosed as a recurring pathology. The 5-year recurrence rate for 86 patients who underwent initial surgery was 7.27%. Single factor analysis revealed that the course of disease, bone destruction, invasion of surrounding tissues, tumor size, capsule integrity, and expression of Ki-67 were statistically significant (P<0.05). Binomial Logistic regression analysis showed that capsule integrity was a risk factor influencing recurrence (P=0.008). CONCLUSION: LGPA has a risk of recurrence and potential for malignant transformation. Complete removal of the tumor and capsule in the initial surgery is a key factor in preventing recurrence.